INTEGRATED MARKETING COMMUNICATION PT. PERTAMINA DALAM MEMBANGUN BRAND AWARENESS PRODUK BRIGHT GAS 5,5 KG PADA MASYARAKAT KOTA PEKANBARU - Handayani, Septia; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Bright gas 5.5 kg is the latest product launched by PT. Pertamina in early February 2017 at SKA Mall Pekanbaru. Bright gas 5.5 kg is a non-subsidized LPG type and has advantages that can distinguish it from previous LPG types. In communicating the bright gas product 5.5 kg to the people of Pekanbaru society, PT. Pertamina conducts a series of marketing communications activities by applying the concept of Integrated Marketing Communication (IMC). The public looks enthusiastic about the bright gas 5.5 kg and the enthusiasm is certainly related to the brand awareness that is built in the society, which is people start to know the bright gas from various news in newspapers and also see the ads on TV. The purpose of this research is to know the implementation of IMC elements conducted by PT. Pertamina in building brand awareness of bright gas product 5.5 kg in Pekanbaru society and to know the form of integration of IMC elements implementation at PT. Pertamina in building brand awareness bright gas product 5.5 kg in Pekanbaru society.This research is using qualitative methods. This research was conducted at Branch Marketing of PT. Pertamina Riau at Sisingamangaraja street No. 141 Pekanbaru. Informant bleaching is done by purposive technique. Using data collection techniques through observation, interviews, and documentation. Meanwhile, to test the validity data, researcher using extension of participation and triangulation.The result of this research is, in building brand awareness of bright gas product 5.5 kg in Pekanbaru city society, PT. Pertamina uses only five of the six IMC elements that is advertising, sales promotion, publicity, direct marketing and interactive marketing. While, the form of integration conducted is existing division unit of PT. Pertamina to operate marketing communication program of bright gas product 5,5 kg and other forms of integration is from the messages such as logo, image and specification of bright gas product 5.5 kg which is designed with shades of pink in accordance with the concept of the products delivered on each IMC elements performed. Overall IMC implemented by PT. Pertamina can be quite good. Which is brand awareness that building in Pekanbaru society at this time is up to level of brand recognition. Which is people have been able to describe the product specifications of bright gas 5.5 kg.Keyword: Integrated Marketing Communications, Brand Awareness, Bright Gas 5.5 kg